Digestive properties of half‐fin anchovy hydrolysates/glucose Maillard reaction products and modulation effects on intestinal microbiota. (3rd November 2021) - Song, Ru; Shi, Min; Gu, Luo
Abstract: BACKGROUND: The consumption of dietary Maillard reaction products (MRPs) might lead to positive or negative effects on health. The digestibility of half‐fin anchovy hydrolysates/glucose MRPs (HAHp(9.0)‐G MRPs) was therefore determined. The intestinal microbiota modulation of HAHp(9.0)‐G MRPs in mice was also evaluated after administration for 14 days (1 g kg −1 bodyweight). RESULTS: Different levels of digestibility of MRPs of fructosamine and advanced glycation products of N ε ‐carboxymethyllysine were detected in HAHp(9.0)‐G MRPs during simulated gastrointestinal digestion. An increased relative proportion of soluble fluorescent melanoidins (SFMs) was observed during gastric digestion as compared to that in the original HAHp(9.0)‐G MRPs, followed by decreases in SFMs in intestinal digestion. After feeding with HAHp(9.0)‐G MRPs for 14 days, increased goblet cells were observed in the ileum regions of female and male mice. High‐throughput 16S ribosomal RNA gene sequencing of fecal samples revealed that HAHp(9.0)‐G MRPs administration increased the density of the phylum Bacteriodetes and reduced the density of the phylum Firmicutes in male mice. By comparison, a relatively higher density of members of the phylum Saccharibacteria was observed in female mice. A consistent increase in the abundance of Bacteroidales_S24‐7_group_norank was found in female and male groups fed with HAHp(9.0)‐G MRPs. Female and male mice treated with HAHp(9.0)‐G MRPs also showed higher levels of propionic and butyric acids in feces than their corresponding controls. CONCLUSION: Half‐fin anchovy hydrolysates/glucose MRPs can be partly hydrolyzed in the simulated gastrointestinal digestion system. Treatment with HAHp(9.0)‐G MRPs induced sex‐related differences in bacterial abundance and diversity in mice; however, the up‐regulation of anti‐inflammatory activity was predicted in both female and male mice. © 2021 Society of Chemical Industry.